Mauritania : Financial/Private Sector Capacity Building - Mohan, P. C. (World Bank, Washington, DC, 2012)
The objective of the Financial/Private Sector Capacity Building project (1995-2000) was to assist the Government of Mauritania in implementing a program of private sector promotion through strengthening the legal and regulatory framework and creating an enabling environment for private investment. The project was put in place at a time when major macro-economic imbalances had already been addressed and it extended and deepened reforms initiated under the adjustment program in the mid-1980s. It focused on activities which (i) encourage investor interest in the private sector, particularly in mining and fishing by, for example, revising commercial and tax codes ; and (ii) strengthen the financial sector for providing better credit and banking services needed for the development of private sector activities. Lessons learned focused on genuine stakeholder participation to achieve intended objectives. Mauritania has modernized its business law without any conflict with Islamic law thanks to the involvement of traditional magistrates in the law preparation process. It would have been helpful to have limited the number of executing agencies involved in delivering the several complex components. Institutional change, particularly in the context of limited capacity, requires long-term action. Lastly business incentives should not be reduced to a special tax regime.